Implantable Neural Prostheses 2 Techniques and Engineering Approaches - Zhou, David; Greenbaum, Elias; SpringerLink (Online service) (New York, NY : Springer New York, 2010)
This book and its companion volume describe state-of-the-art advances in techniques associated with implantable neural prosthetic devices and their applications. They offer researchers, engineers, clinicians, students and any specialists in this field a deeper understanding of the neural prosthetic techniques currently available for a wide range of biomedical applications. In part two of this two-volume sequence, Implantable Neural Prostheses: Techniques and Engineering Approaches, the focus is on general techniques, platforms, and engineering approaches in research and development. Coverage includes biocompatibility, electrode materials and testing, electrochemical techniques for neural stimulation applications, thin-film electrode arrays, hermetic and thin-film packaging, and microelectronics for recording, stimulation and wireless telemetry. Also discussed is the design process in the development of medical devices.
The Biocompatibility and Biostability of New Cardiovascular Materials and Devices -- Technology Advances and Challenges in Hermetic Packaging for Implantable Medical Devices -- Science and Technology of Bio-Inert Thin Films as Hermetic-Encapsulating Coatings for Implantable Biomedical Devices: Application to Implantable Microchip in the Eye for the Artificial Retina -- The Electrochemistry of Charge Injection at the Electrode/Tissue Interface -- In Situ Characterization of Stimulating Microelectrode Arrays: Study of an Idealized Structure Based on Argus II Retinal implants -- Thin-Film Microelectrode Arrays for Biomedical Applications -- Stimulation Electrode Materials and Electrochemical Testing Methods -- Conducting Polymers in Neural Stimulation Applications -- Microelectronics of Recording, Stimulation, and Wireless Telemetry for Neuroprosthetics: Design and Optimization -- Microchip-Embedded Capacitors for Implantable Neural Stimulators -- An Effective Design Process for the Successful Development of Medical Devices.
Keywords: ENGINEERING; NEUROSCIENCES; BIOMEDICAL ENGINEERING; BIOMATERIALS; ENGINEERING; BIOMEDICAL ENGINEERING; BIOPHYSICS AND BIOLOGICAL PHYSICS; NEUROSCIENCES; BIOMATERIALS